Evaluation of Biofilm Formation in Molecular Identification E. coli Strains that Cause Urinary Tract Infection in Children and Antibiotic Resistance - Anfal Shakir Motib; Muhamed Aydin Abbas; Mohammed Shakir Motib; Mohammed Hussein Jaber (Diyala Journal of Medicine, 2025)
Background: Escherichia coli (E. coli) is the primary causative agent of urinary tract infections (UTIs), one of the most common human illnesses, which frequently occurs in children. Objective: This study aimed to identify E. coli strains that cause UTIs in children and determine the correlation between biofilm formation and antibiotic resistance. Patients and Methods: A total of 290 cases of UTI patients were collected from Al-Batoul Teaching Hospital in Diyala, Iraq. The ages of these patients ranged from 1 day to 12 years, from February 2023 to January 2024. The strains of E. coli that cause UTIs were identified using polymerase chain reaction (PCR) and sequencing methods. Antimicrobial susceptibility was evaluated, and a microtiter plate assay was used to assess biofilm production. Results: The predominant bacteria responsible for UTI in children were E. coli (40%), and it was noted that the lowest percentage of bacteria causing UTI in this study were Klebsiella oxytoca and Pseudomonas aeruginosa, as they appeared in 5% of cases. The strains of E. coli that cause UTIs in the current study are E. coli Y8-2 (14.8%), E. coli 106K88 (19.3%), E. coli UA32 (11.4%), E. coli RM11911 (20.5%), and E. coli EC1704-1 (34%). E. coli EC1704-1 showed multidrug resistance (MDR) to ciprofloxacin (100%), sulfamethoxazole-trimethoprim (100%), cephalosporins and penicillin (100%), and aminoglycosides (93.3%). E. coli Y8-2, E. coli 106K88, and E. coli UA32 appeared less resistant to antibiotics than E. coli EC1704-1 and E. coli EC1704-1. Additionally, it was demonstrated that biofilm formation and antimicrobial resistance were negatively correlated among the isolates. Conclusion: This study demonstrated a clear link between biofilm formation and antibiotic resistance, suggesting that this bacterium with reduced resistance may depend on biofilms to enhance its survival. Keywords: 16SrRNA, Escherichia coli strains, Antibiotic resistance, Urinary tract infection, Biofilm formation.